PENGARUH PEMBERIAN INSENTIF, DISIPLIN KERJA, DAN TINGKAT PENDIDIKAN TERHADAP KINERJA KARYAWAN PADA LEMBAGA LAYANAN PENDIDIKAN TINGGI XIII ACEH - Teja Yus Putra; Wirdah Irawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
Abstract: This study aims to measure the effect of incentive, work discipline, and education levels to employee performance at Lembaga Layanan Pendidikan Tinggi XIII Aceh. The sample used in this study were employee is totaling 87 respondents. Data equipment used in this study was a questionnaire. The sampling technique used is saturation sampling. Multiple Linear Regression was used as method of analysis to determine the effect of all the variables involved. Based on the results of the Multiple Linear Regression indicated that incentive, work discipline, and education levels positively influence employee performance.